Participatory management of weed infestation in Lake Tana - setting a better future in the front mirror - Sewunet, Birhanu; Girma, Haileyesus; Debela, Sisay Abebe; Luke, Amana Ogeto; Gebrehiwot, Mesfin (Frontiers in Ecology and Evolution, 2022)
Lake Tana is one of the biosphere reserves in Ethiopia registered by the United Nations Educational, Scientific, and Cultural Organization (UNESCO). Water hyacinth is expanding in the lake owing to increased nutrient load from the watershed. As efforts from the government alone could not bring the anticipated change, local peoples’ engagement and contribution are believed to sustainably and effectively manage the watershed, and hence prevent the spreading of the weed. This study, therefore, aims to estimate households’ contribution (willingness to pay –WTP– and willingness to contribute labor – WTCL–) to prevent and control water hyacinth, and hence improve lake ecosystem services through a hypothetical watershed management in Lake Tana. This study applied quantitative and qualitative methods. It was conducted among 560 randomly selected households of the Libo-kemkem district using a contingent valuation method from March to April/2021. Eleven key informant interviews were also conducted. Bivariable and multivariable interval regression models were used to identify the determinants of households’ potential contribution. Thematic analysis was used to analyze the qualitative data. As the weed is believed negatively impacting the ecosystem services provided by the lake, 72% of the respondents showed willingness to contribute to the proposed management program. About 32% and 39% of the respondents were willing to pay in cash and to contribute in labor, respectively, to prevent the weed infestation. On the other hand, 28% of them were neither willing to contribute in cash nor in labor to the hypothetical market. The findings showed that the mean annual WTP and WTCL of respondents were 632.7 ETB and 30.1 man-days per household, respectively. The place of residence, educational status, farm plot area, household income, family size, and conference participation significantly influenced WTP and/or WTCL. In this hypothetical improvement scenario, an estimated annual WTP and WTCL of nearly twelve million Ethiopian birr and seven hundred man-days per year, respectively, are reported considering the total households in the study area. Therefore, collaborative efforts by different stakeholders are next steps to realize the hypothetical contributions.